American Cinema of the 1960s : Themes and Variations - Grant, Barry Keith, 1947- (Book collections on Project MUSE., 2008)
The profound cultural and political changes of the 1960s brought the United States closer to social revolution than at any other time in the twentieth century. The country fragmented as various challenges to state power were met with increasing and violent resistance. The Cold War heated up and the Vietnam War divided Americans. Civil rights, women?s liberation, and gay rights further emerged as significant social issues. Free love was celebrated even as the decade was marked by assassinations, mass murders, and social unrest. At the same time, American cinema underwent radical change as well.